Upaya Guide untuk Mengedukasi Pengunjung dalam Atraksi Arung Jeram Situmandi di Desa Hutabarat, Kecamatan Tarutung, Kabupaten Tapanuli Utara - Melkisedek wuwute; Ade Putera Arif Panjaitan; Yulia k.s Sitepu (Tamasya : Jurnal Pariwisata Indonesia, 2025)
This study aims to determine: Guide's efforts to educate visitors in the Situmandi White Water Rafting Attraction in Hutabarat Village, Tarutung District, North Tapanuli Regency. The type of research used is qualitative research. The sample in this study was the Situmandi tourist attraction. The results of the study show: Guide's efforts to educate visitors in the Situmandi white water rafting attraction in Hutabarat Village, Tarutung District, North Tapanuli Regency are more focused on creating promotional media such as creating social media such as Facebook, Instagram, WEBSite, Tiktok and Banners This method is one of the promotional methods that can attract the attention of Guide's efforts to educate visitors to the Situmandi tourist attraction. From various aspects that provide specific opinions: in Hutabarat Village, Tarutung, North Tapanuli Regency. There are several inhibiting factors that researchers found from statements and those felt by the Hutabarat Village Government, including Promotion, tourist attractions, Facilities,